The Merry Adventures of Robin Hood - Howard Pyle
From the Author to the Reader KOU wko so plod amid serious things that you feel it shame to give yourself up even for a few short moments to mirth and joyousness in the land of Fancy ;you who think that life hath nought iodo with innocent laughter that can harm no one; these pages are not fffryou. Clap to the leaves and go no farther than this, for I tell you plainly that if you go farther you will be scandalised by seeing good, sober folks of real history so frisk and caper in gay colors and motley, that you would not know them but for the names tagged to them. Here is a stout, lusty fellow with a quick temper, yet none so ill for all that, who goes by the name of Henry II. Here is a fair, gentle lady before whom all the others bow and call her Queen Eleanor. Here is a fat rogue of a fellow dressed up in rich robes of a clerical kind, that all the good folk call my Lord Bishop of Hereford. Here is a certain fellow with a sour temper and a grim look the worshipful, the Sheriff of Nottingham. And here, above all, is a great, tall, merry fellow that roams the greenwood and joins in homely sports, and sits beside the Sheriff at merry feast, which same beareth the name of the proudest of the Plantagenets Richard of the Lions Heart. .R eside these there are a whole host of knights, priests, nobles, burghers, yeomen, pages, ladies, lasses, landlords, beggars, pedlers, and what not, all living the merriest of merry lives, and all bound by nothing bu a few odd strands of certain old ballads snipped and clipped and tied togetlur again in a score of knots) which draw these jocund fellows here and there, singing as they go.